Designing Operational Standards For Lost And Found Handling Procedures In The Front Office Department At The Poliwangi Jinggo Educational Hotel - Rini Marliza; Rachma Amalia, Firda; Nurhalimah, Nurhalimah (Jurnal Ekonomi, 2024)
This research aims to design a lost and found SOP at the Poliwangi Jinggo educational hotel, as a written guideline for staff in handling the process of losing and finding guest items so that all staff can handle lost and found more regularly and in accordance with the established SOP. Because up to now, the handling of lost and found has only been based on the knowledge or experience of the staff, without any written guide-lines from the hotel directly. The design process begins with collecting data from informants who are experienced in handling lost and found and hotel staff so that researchers can prepare lost and found SOPs accord-ing to the situation and conditions that are appropriate for hotel. Next, the data is analyzed using the Miles and Huberman method, first data collected becomes a process flow by reduction stage, second process flow is arranged in the form of a flowchart by presentation stage, and the last, the flowchart design are verified and validated by conclusion closing stage. The result of the conclusion is that the lost and found SOP is stat-ed to be in accordance with the hotel's needs and can be applied in the hotel environment. The SOP has also been prepared in the form of a complete flowchat with detailed explanations so that staff can under-stand the handling sequence from start to finish quickly and easily. By having a written lost and found SOP, each staff can learn and understand how to handle lost and found by the same guidline. The existence of a lost and found SOP can remind the staff's performance in handling lost and found effectively and efficiently, so as to build a sense of satisfaction and trust in guests regarding security during their stay at the Poliwangi Jinggo educational hotel.